Traffic injury mortality trends in children and adolescents in Lithuania among road users - Strukcinskiene, Birute; Uğur-Baysal, Serpil; Raistenskis, Juozas (The Turkish Journal of Pediatrics, 2014)
This study analyzes traffic mortality trends among road users from 1998 to 2012 in children and adolescents aged 0-19 years in Lithuania. National mortality data of pedestrians, cyclists, motorcyclists, and car occupants were used to compare trend lines. The study revealed that 56% of the deceased in road traffic crashes were car occupants, while 24% were pedestrians. The incidence of death from traffic injury was 2.5 times higher in boys than girls. Traffic injury mortality and pedestrian mortality rates declined significantly in the total group. There was also a significant decline in mortality among cyclists for the total group and female subgroup. Trends in mortality rates among motorcyclists and car occupants showed no significant changes. A long-term decline is more likely to be affected by efforts in the promotion of sustainable and permanent road safety. The reduced risk exposure may also have been influenced by the economic recession.